PENGENDALIAN PERSEDIAAN SPARE PART BIDANG MEKANIKAL DAN ELEKTRIKAL DENGAN METODE ACTIVED BASED COASTING (ABC) DAN ECONOMIC ORDER QUANTITY (EOQ) PADA PT. STP UNIT SOBO BANYUWANGI - Eritrian Bisma Primayanda; Herdiana Dyah; Harliwanti Prisilia (J-ENSITEC, 2024)
PT. Suri Tani Pemuka (STP) is a pond company in Banyuwangi that has various departments according to their tasks and functions, one of which is the mechanical and electrical (ME) department. In carrying out its tasks, the ME department heavily relies on the need for spare parts in repairing machine breakdowns in the workshop. However, there is a constraint faced, namely the delay of spare parts in repairing water turbine machine breakdowns due to lack of inventory control, especially for water turbine machine spare parts. Therefore, the Active Based Coasting (ABC) and Economic Order Quantity (EOQ) methods are used to solve this problem. The aim of this research is to determine the level of spare parts inventory based on cost, the level of spare parts inventory based on forecasting results, and to determine the ideal economic ordering calculation in spare parts inventory. The results of implementing ABC still show delays in spare parts inventory. After being improved using EOQ, the EOQ calculation results are as follows: Gear box gear 13 units, Gear box bearing 41 units, Turbine fan 6 units, Electric motor bearing 19 units, Seal cover 19 units, Oil seal 38 units, Turbine clutch 4 units. The implementation of the EOQ method in the inventory system or application shows that its use can reduce the expenditure of ordering goods more efficiently and effectively than relying solely on the ABC method.